(untitled) (Revista Sistemas de Producción Agroecológicos, 2025)
Corn (Zea mays L.) is a crop of global importance, due to its multiple uses. In Argentina, one of the main producers in the world, its yield is affected by various pests and diseases. The mass adoption of Bt corn in this country has raised concerns about pest resistance, such as possible alterations in the composition of the entomofauna. In this context, it is necessary to investigate whether the predominance of Bt corn has generated changes in the populations of pests and natural enemies. This is why this study aimed to determine the economically important phytophages and beneficial predators in a non-genetically modified corn crop in the province of Córdoba, Argentina. The experiment was carried out in the Field School of the Faculty of Agricultural Sciences of the National University of Córdoba, located in the town of Capilla de los Remedios. A non-Bt corn RFG22RE (Corteva) was planted on December 28, 2023. The experimental design consisted of three plots of 7 rows 5 meters long, separated by 0.52 m, with weekly sampling from emergence to physiological maturity, totaling 12 evaluations. Two samples of 10 consecutive plants were taken, manually checking for insects and egg masses, representing a total of 20 plants per plot/evaluation. The most important lepidopteran phytophagous of the crop was Spodoptera frugiperda, which presented the highest incidence and severity in the phenological stage V6-V7. The sampling revealed a significant increase in Dalbulus maidis, a species that until now had no economic importance in the region. This increase was accompanied by a higher incidence of stunting disease, which shows its impact on corn cultivation. The absence of Diatraea scharalis in the crop, despite being a non-Bt corn, suggests changes in the population dynamics of this pest at a regional level, which should be studied. The most frequent species within the predator group was Chrysoperla sp. The results of this work highlight the importance of carrying out constant monitoring of crops, especially with the appearance of new species or changes in the distribution of those already established. It is necessary to evaluate the broader effects on the insect community to anticipate resistance problems and maintain sustainable management strategies. Keywords: natural enemies; non-Bt corn; monitoring; pests.